Pengaruh Pembelajaran Pendidikan Agama Kristen Terhadap Hasil Belajar Siswa pada Mata Pelajaran Lainnya - Silas Sudarman; Candra Nugraha Wati (Voice, 2024)
Christian Education plays an important role in students’ holistic lives. Schools need to pay attention to Christian Education so that it can run well and have an impact on students’ lives. This study aims to determine the effect of Christian Education on student learning outcomes in other subjects. Sampling using simple purposive sampling technique. The population is students of class VIII from 32 junior high schools in Salatiga. From those 32 junior high schools, one representative school was selected that has equivalent academic abilities. This study uses a quantitative method design with an ex post facto design. The data analysis technique uses simple regression analysis with the help of the SPSS 24 application. The results of this study show that the significance value (Sign.) of the variable is 0.284> 0.05, which means that the value is greater than 0.05. Thus, it can be concluded that the hypothesis H0 in this study is accepted, namely that the Christian Education learning variable (X) does not affect student learning outcomes in other subjects in junior high schools in Salatiga (Y).